Tantrum Behavior Modification for Autistic Student at Secondary School Using Social Stories Technique - Noriah Binti Sha'arani; Mohd Mokhtar Tahar (Department of Special Education, 2017)
Autistic children have some social problems including weakness in bilateral interaction, communication problems and lack of imagination. The objectives of this study were to examine the effectiveness of social stories technique in reducing the duration of a student autistic tantrum and elimination of the problem tantrum. This study is a case study that builds quantitative behavior classical conditioning theory expounded by Ivan Pavlov and combined with the ADDIE Model. Observations carried out over a period of 20 days to see the effectiveness of social stories technique for changing the negative behavior of autistic students studying in a secondary school. The method of A-B where A represents the baseline phase and B-phase intervention represents. Social stories read to sample every day before the teaching begins within 10 minutes. The results of this study found that social stories technique successfully reduced the tantrum behavior study. However, tantrum behavior is still failing to be completely eliminated, but there is a significant reduction of the behavior. Through this study, it was found the use of social stories can reduce negative behaviors in autistic teenager. It is hoped that this study can serve as a guide and ideas for teachers to diversify the techniques to modify negative behavior among pupils in special education. We hope this study can be uplifting and inspiring teachers that negative behavior autistic students can be changed with the right technique.